Looking at sports: Values and strategies for international management - Gerd Nufer; Ann-Christin Reimers (Hochschule Reutlingen, ESB Business School, 2011)
Although sport is generally defined as motor activity, it has always been much more than that. Many years ago, people already contrasted the games against the more serious demands of employment or against military conflicts, which led to a special status of sports that lasts until today. Since management and sports follow the same objective of achieving highest performance, correlations between these two fields nowadays become increasingly interesting in terms of corporate and business unit strategy. This elaboration aims to point out how organizations as well as individuals can benefit from the general and psychological values and strategies of professional sports, by first looking at the general framework of professional sports and further applying approaches from various types of sports directly to certain business areas.
urn:nbn:de:bsz:21-opus-54360
Keywords: 650